Penguatan Usaha Mikro, Kecil Dan Menengah (UMKM) Rumahan Desa Karimunting Melalui Sosialisasi Branding Dan Online Marketing - Ria Veilyzia; Heriyadi Heriyadi; Ervia Claudia; Julia Hasanah; Marsya Alya Putri; Dian Surlita (Pusat Riset dan Inovasi Nasional, 2025)
Home-based MSMEs play a strategic role in supporting rural economies, yet they continue to face challenges related to strengthening product identity and limited access to digital marketing. This community service activity was carried out in Karimunting Village with the aim of empowering MSMEs through branding and digital marketing awareness. The approach was conducted directly from house to house to reach business owners personally and foster more intensive communication. The implementation method included initial observation, preparation of outreach materials, door-to-door education, and evaluation through discussions and participant feedback. The materials delivered covered the importance of creating business logos, developing product catalogs, and utilizing social media as well as marketplaces as digital marketing platforms. The results showed that the majority of MSME owners felt supported in understanding the importance of product identity and had begun to try marketing their products online. This program serves as an initial foundation for the development of digital-based home-based MSMEs.